Global Fixed-Time Horizontal Tracking Control of AUV Under Parameter Perturbation and Input Quantization - Sunwei Jiang; Shuxuan Liu; Zhicheng Liu; Quanming Miao (IEEE Access)
This paper investigates the horizontal trajectory tracking problem of an autonomous underwater vehicle (AUV) subject to parameter perturbations and ocean current disturbances. A fixed-time integral sliding mode control method is proposed, incorporating a disturbance observer. By integrating the backstepping technique with non-singular terminal sliding mode control, composite disturbances are estimated using a fixed-time neural network disturbance observer. A fixed-time sliding mode controller is designed along with the sliding mode surface. To enhance tracking performance, fixed-time reaching laws are developed, ensuring that tracking errors converge to a smaller range near the origin within a fixed time. To mitigate chattering during signal quantization, a hysteretic quantizer is employed to process input variables. Rigorous theoretical analysis is conducted using Lyapunov stability theory. Simulation results demonstrate the effectiveness of the proposed controller, exhibiting improved robustness and faster convergence under parameter perturbations and external disturbances.